A lithium primary battery
Patent Information
- Application Number
- CN202611231631.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-30
AI Technical Summary
但但锂盐类磺酰胺添加剂亲水性强、水分敏感度高,极易发生水解反应,不仅造成自身有效成分失效,还会生成腐蚀性酸性物质,腐蚀电极材料并引发电芯产气鼓包,同时破坏电解液体系稳定性,显著缩短电池使用寿命,也大幅提升了电池生产过程中的无水环境管控难度与加工成本;并且磺酰胺类及磺酰亚胺类化合物导电性能较差,为在电极表面形成稳定的SEI膜,通常需要提高其添加量,磺酰胺锂以及磺酰亚胺锂添加量偏大会造成体系内锂离子浓度过高,电解液粘度增大,电池自放电率增大;磺酰胺或磺酰胺添加量过多会直接增大电池内阻,劣化电池低温放电性能;反之若添加量过低,又会造成SEI膜成膜速率缓慢,膜层结构稳定性不佳
1)与电解液内添加磺酰胺类或磺酰亚胺类添加剂相比,通过负极表面改性膜的形式引入磺酰胺类或磺酰亚胺添加剂可以减少添加剂的用量,有效避免电池内阻的升高,适量的磺酰胺类或磺酰亚胺添加剂与锂离子结合形成络合物,能够减小电池在低温放电过程中锂离子迁移电极/电解液界面过程中的能垒,提升锂离子迁移速率,进而提升电池低温条件下的放电性能;
Smart Images

Figure CN123018009A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to battery processing technology, and more particularly to a lithium primary battery. Background Technology
[0002] Lithium-manganese primary batteries possess advantages such as high specific energy, low self-discharge rate, economy, and a wide operating temperature range, leading to their widespread application in various fields, including car keys and remote medical devices. In recent years, with the emergence of new application scenarios, batteries need to meet the demands of more demanding environments, with storage characteristics and discharge performance under extreme temperatures being particularly important. At high temperatures, batteries experience a series of problems, including electrolyte decomposition and gas generation on electrode surfaces, decreased interfacial film stability, and dissolution of positive electrode active materials. At low temperatures, issues arise such as increased electrolyte viscosity, reduced positive electrode material activity, and thickening of the negative electrode passivation film. These factors can easily lead to increased resistance, exacerbate self-discharge, and ultimately affect the battery's discharge characteristics.
[0003] Chinese patent CN101877410B discloses a method for improving battery discharge performance and high-temperature storage stability by modifying the surface of a lithium metal anode with fluorinated carbon microparticles. The fluorinated carbon / lithium fluoride component in this modified layer can, to some extent, suppress side reactions between the electrolyte and the electrode at high temperatures. However, due to the poor conductivity of lithium fluoride, it affects rate performance, increases interfacial impedance, reduces lithium-ion transport rate, and leads to a decline in battery rate performance. The introduction of fluorine atoms may generate hydrogen fluoride inside the battery, which can accelerate the dissolution of manganese in the positive electrode and damage the SEI film. Therefore, strict moisture control is required during the production process, further increasing the difficulty of the manufacturing process.
[0004] Chinese patent application CN114188607A discloses an electrolyte additive containing a sulfonamide structure. Its decomposition products are rich in heteroatoms such as S, N, and O, which helps to generate a stable inorganic SEI film and is beneficial for lithium-ion conduction at low temperatures. The electrolyte using this additive can capture hydrofluoric acid, reduce the corrosion of the positive electrode material by hydrofluoric acid, stabilize the interface structure, and thus improve the overall performance of lithium-ion batteries, especially the electrochemical performance at low temperatures. However, lithium salt sulfonamide additives are highly hydrophilic and sensitive to moisture, making them prone to hydrolysis. This not only degrades their own effective components but also generates corrosive acidic substances that corrode electrode materials and cause cell bulging. Simultaneously, it disrupts the stability of the electrolyte system, significantly shortening battery life and greatly increasing the difficulty and cost of controlling the anhydrous environment during battery production. Furthermore, sulfonamides and sulfonylimides have poor conductivity, requiring increased dosage to form a stable SEI film on the electrode surface. Excessive addition of lithium sulfonamides or lithium sulfonylimides results in excessively high lithium-ion concentrations, increased electrolyte viscosity, and increased battery self-discharge rate. Excessive sulfonamide or sulfonamide addition directly increases battery internal resistance and degrades low-temperature discharge performance. Conversely, insufficient addition leads to slow SEI film formation and poor film structure stability.
[0005] In summary, developing a lithium primary battery that combines good high-temperature storage stability with low-temperature discharge performance and low cost is of significant practical importance and research value. Summary of the Invention
[0006] The purpose of this invention is to provide a primary lithium battery.
[0007] The technical solution to achieve the objective of this invention is: a primary lithium battery, comprising a snap-fit negative electrode cap and a positive electrode shell, wherein a negative lithium electrode sheet, a separator, a positive electrode sheet, and a current collector are sequentially disposed between the negative electrode cap and the positive electrode shell, and a negative electrode surface modification film is disposed between the negative lithium electrode sheet and the separator, wherein the areal density of the negative electrode surface modification film is 5-21 g / m³. 2 The modified film on the negative electrode surface is prepared using raw materials in the following weight ratio, with each component expressed in parts by weight: Conductive carbon material 2.4–4.8%; Adhesive 0.02-0.1%; Additives 2.4-4.8%; Solvent content: 90.3%–95.1%; The conductive carbon material comprises any one or more combinations of graphite, acetylene black, Ketjen black, graphene, carbon nanotubes, and porous carbon; the binder comprises at least one of polyvinylidene fluoride, nitrile rubber, polystyrene-butadiene rubber, and polytetrafluoroethylene; the additive is a sulfonamide compound or a sulfonylimide compound; and the solvent is one or more combinations of water, methanol, ethanol, propanol, isopropanol, and N-methylpyrrolidone. The preparation method of the negative electrode surface modified film includes: 1) weighing each raw material according to the raw material ratio, first adding the binder to the solvent, then adding the conductive carbon material to the solvent and mixing it evenly, and then adding the additive and mixing it evenly to obtain a slurry; 2) drying the slurry obtained in step 1), and pressing the dried powder into a solid film at a dew point of -40°C.
[0008] Furthermore, step 2) of the method for preparing the modified film on the negative electrode surface can also be to spray the slurry obtained in step 1) onto the surface of the negative electrode lithium sheet, and then dry it to form a thin film attached to the surface of the negative electrode lithium sheet.
[0009] Furthermore, the additive is any one of p-nitrobenzenesulfonamide, p-chlorobenzenesulfonamide, and o-benzoylsulfonamide.
[0010] Furthermore, the mass ratio of the conductive carbon material to the additive is 1:1. Since the additive is non-conductive, an excess of the additive will increase the initial internal resistance of the battery; an excess of conductive carbon material will prevent the internal SEI film of the battery from reaching its optimal state, leading to instability during high-temperature storage and reduced battery discharge characteristics.
[0011] Furthermore, the areal density of the modified film on the negative electrode surface is 8–13 g / m³. 2 Within this areal density range, both the battery's internal resistance and the low-temperature pulse discharge voltage after storage are improved.
[0012] Furthermore, the diameter of the modified film on the negative electrode surface is no larger than the diameter of the negative electrode lithium sheet, to avoid material waste.
[0013] This invention mixes conductive carbon materials with sulfonamide or sulfonylimide compounds to form a solid negative electrode surface modification film that adheres to the inner surface of the negative electrode, creating a high-concentration additive region on the surface of the lithium negative electrode sheet. This has the following beneficial effects: 1) Compared with adding sulfonamide or sulfonimide additives into the electrolyte, introducing sulfonamide or sulfonimide additives through a modified film on the negative electrode surface can reduce the amount of additives used, effectively avoiding the increase of battery internal resistance. An appropriate amount of sulfonamide or sulfonimide additives can combine with lithium ions to form complexes, which can reduce the energy barrier of lithium ion migration at the electrode / electrolyte interface during low-temperature discharge, improve the lithium ion migration rate, and thus improve the discharge performance of the battery under low-temperature conditions. 2) During the high-temperature aging process of primary lithium batteries, sulfonyl groups and sulfonylimides can undergo deprotonation reactions to form a stable and dense composite SEI film with the surface of the negative electrode lithium sheet. This effectively suppresses side reactions inside the battery at high temperatures. The sulfur atoms in the group can improve the lithium ion transport rate, resulting in excellent ion conductivity. This reduces the risk of dendrites piercing the separator and prevents the electrolyte from undergoing side reactions with lithium metal at high temperatures, thereby improving the high-temperature storage characteristics of the battery. 3) Composition design combined with pressing process can control the thickness of the modified film on the negative electrode surface to a relatively thin range, resulting in a lithium primary battery with excellent low-temperature discharge and high-temperature storage performance. 4) Sulfonamide compounds and sulfonylimide compounds are common chemical raw materials with a cost far lower than electrolyte additives such as lithium sulfonamide salts. This invention can meet the requirements of battery characteristics while reducing battery costs. Attached Figure Description
[0014] Figure 1 This is a cross-sectional view of the primary lithium battery described in Embodiment 1 of the present invention; Figure 2 The graph shows the change in internal resistance of the batteries obtained in Example 1 and Comparative Example 1 of this invention when stored at 125°C. Detailed Implementation
[0015] The preferred embodiments of the present invention will be described in detail below. Example 1
[0016] like Figure 1 As shown, a primary lithium battery includes a snap-fit negative electrode cover 1 and a positive electrode shell 2. A negative electrode lithium sheet 3, a negative electrode surface modification film 4, a separator 5, a positive electrode sheet 6, and a current collector 7 are sequentially disposed between the negative electrode cover 1 and the positive electrode shell 2. The negative electrode surface modification film is prepared from raw materials in the following weight ratio, with each component expressed in parts by weight: Conductive carbon materials: 4.8%; Adhesive 0.1%; Additives 4.8%; Solvent 90.3%; The conductive carbon material is composed of graphite and porous carbon in a mass ratio of 1:1; the binder is polystyrene-butadiene rubber; the additive is p-nitrobenzenesulfonamide; and the solvent is water and isopropanol. The preparation method of the negative electrode surface modified film includes: 1) weighing each raw material according to the aforementioned raw material ratio, first adding the binder to the solvent, then adding the conductive carbon material to the solvent and mixing it evenly, and then adding the additive and mixing it evenly to obtain a slurry; 2) drying the slurry obtained in step 1), and pressing the dried powder into a solid film with a thickness of 20μm and a mass of 1.5mg by a hydraulic press at a dew point of -40℃.
[0017] Examples 2-7 Examples 2-7 have the same product structure as Example 1, and the preparation process of the negative electrode surface modified film is the same. The difference lies in the different component design, as shown in Table 1.
[0018] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not have a negative electrode surface modification film, and p-nitrobenzenesulfonamide additive is added to the electrolyte. The amount of p-nitrobenzenesulfonamide additive is the same as that in Example 1.
[0019] Comparative Example 2 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 did not have a negative electrode surface modification film, and no sulfonamide compound or sulfonylimide compound was added to the electrolyte.
[0020] Comparative Examples 3-4 Comparative Examples 3-4 have the same product structure as Example 1, and the preparation process of the negative electrode surface modified film is the same. The difference lies in the different composition design of the negative electrode surface modified film. The specific composition design and weight are shown in Table 1.
[0021] Table 1
[0022] After high-temperature storage tests, high-temperature and low-temperature pulse tests were conducted on the lithium primary batteries of model CR2032 obtained in Examples 1-7 and Comparative Examples 1-4. This invention also provides Comparative Example 5, which differs from Example 1 only in that the diameter of the negative electrode surface modification film (16.2 mm) in Comparative Example 5 is larger than the diameter of the negative electrode lithium sheet (15.9 mm), to verify the influence of the diameter of the negative electrode surface modification film on battery performance.
[0023] The high-temperature storage test involved storing the battery in an oven at 105°C for 500 hours, then removing it and allowing it to cool to room temperature before measuring its characteristics. The high-temperature and low-temperature pulse tests involved storing the battery in ovens at -40°C and 100°C for 30 minutes each, followed by a pulse test using a discharge mode of 500Ω / 0.5s+10mA / 10ms, recording the battery voltage (V) at the end of the pulse. The results are shown in Table 2.
[0024] Table 2
[0025] As shown in Table 2, the average internal resistance of the new batteries in Examples 1-7 was 3-4 Ω, lower than the average internal resistance of 8.68 Ω in Comparative Example 2. The surface-modified film on the negative electrode can construct ion channels inside the battery, effectively reducing the battery's internal resistance. After storage at 105℃ for 500 hours, the change in internal resistance of the batteries in Examples 1-7 was less than 2.5 Ω. Compared with Comparative Example 1 (with nitrobenzenesulfonamide additive added to the electrolyte) and Comparative Example 2 (without nitrobenzenesulfonamide additive added), the high-temperature storage stability was significantly improved. Figure 2 It is evident that the addition of additives to the electrolyte increases the battery's internal resistance, failing to resolve the issue of increased internal resistance during high-temperature storage. This indicates that a stable SEI film has not been formed inside the battery. In contrast, the modified film on the negative electrode surface can effectively form a stable SEI film, and the battery's resistance does not increase abnormally after high-temperature storage.
[0026] Examples 1-7 all showed higher pulse voltage values at -40℃ than Comparative Examples 1-4, indicating that the modified film on the negative electrode surface can effectively promote the formation of the SEI film on the negative electrode. The sulfur element in sulfonamide or sulfonimide compounds can effectively promote the migration of lithium ions, providing higher voltage for the battery. The pulse voltage values at 100℃ were also higher than those in Comparative Examples 1-4, indicating that the modified film on the negative electrode surface reduces the side reactions of the electrolyte on the negative electrode surface inside the battery during high-temperature storage by promoting the SEI film and physical isolation, and the battery did not show a significant decline.
[0027] In Example 4, the average internal resistance of the new battery was 3.31Ω, and the pulse voltage at -40℃ after high-temperature storage was 1.90V. This indicates that when the sulfonyl compound component of the modified film on the negative electrode surface is small, the battery cannot fully react to form a stable SEI film. During high-temperature storage, the number of side reactions inside the battery increases, and the battery discharge characteristics are reduced.
[0028] In Experiment 5, the average internal resistance of the new battery was 4.35Ω, which was higher than that in Example 1. This indicates that the excessive additives in the modified film on the negative electrode surface affected electron transport during discharge, thus increasing the internal impedance of the battery. The pulse discharge voltage at -40℃ after high-temperature storage was 1.94V, which was not higher than that in Example 1. This indicates that the amount of additives used was greater than that of conductive carbon materials, which did not promote the SEI film inside the battery. Instead, it affected ion transport and caused the pulse voltage to decrease.
[0029] Examples 6 and 7 validated the use of a single carbon material. In Example 6, the internal resistance of the new battery was 3.92Ω, and the pulse voltage at -40℃ after high-temperature storage was 1.98V. In Example 7, the internal resistance of the new battery was 4.11Ω, and the pulse voltage at -40℃ after high-temperature storage was 1.82V. The results show that in Example 6, when using a single type of graphite, the internal ion pathway of the battery could not achieve the optimal effect (highest pulse voltage). The reason is that graphite has a layered structure, and the ion transport pathway formed is a layered embedding mode, but it also has the problems of long transport path and small interlayer spacing, which reduces the internal ion migration rate of the battery and thus leads to a decrease in pulse voltage. In Example 7, when only porous carbon was used, due to the small diameter and poor film-forming properties of the spherical carbon, it was impossible to form a three-dimensional ion channel at the microscopic level, resulting in the internal resistance of the new battery and the battery that could be stored at high temperature being greater than other experimental groups, and the low-temperature pulse voltage being lower.
[0030] Meanwhile, in Experiment 1, a modified film was prepared on the negative electrode surface using a spraying process, and then a CR2032 battery was assembled according to the normal procedure. In Comparative Example 1, a CR2032 battery was assembled using an electrolyte containing additives. After both sets of batteries were assembled, a high-temperature storage test was conducted, and the battery internal resistance was measured every 100 hours. The results are as follows: Figure 2 As shown. (Combined with Table 2 and...) Figure 2 As can be seen, the average internal resistance of the new battery in Comparative Example 1 is 7.56Ω, which is significantly higher than that in Example 1. After high-temperature storage, the voltage at -40℃ is 0.95V, indicating that adding sulfonamide additives to the electrolyte does not significantly improve the formation of the SEI film, but instead increases the internal impedance. During discharge, the conductive carbon material in the modified film on the negative electrode surface can provide channels for ion transport. Additives promote the formation of the SEI film and enhance the lithium ion migration rate through functional groups. However, excessive additives will hinder ion channels. When the proportion of additives is too high, the internal impedance of the battery will increase and the pulse discharge voltage of the battery will decrease.
[0031] In Comparative Example 3, the negative electrode surface modified film had no additives, the new resistance was 4.25Ω, and the battery pulse voltage was 1.79V after high-temperature storage. Compared with Example 1, it shows that sulfonamide additives can promote the formation of the battery SEI film and reduce the internal side reactions of the battery during high-temperature storage. Such effects cannot be achieved when only conductive carbon is used.
[0032] In Comparative Example 4, the negative electrode surface modification film lacked conductive carbon material, resulting in a relatively high average internal resistance of 5.25Ω. After high-temperature storage, the pulse voltage at -40℃ was 1.65Ω. Compared with the average internal resistance and -40℃ pulse voltage in Example 1, this indicates that the conductive carbon material in the negative electrode surface modification film constructs ion pathways inside the battery, increases ion migration rate, and effectively reduces battery impedance. The negative electrode surface modification film, with only sulfonamide or sulfonimide compounds, cannot achieve the most effective result.
[0033] In Comparative Example 5, when the diameter of the modified film on the negative electrode surface is larger than the diameter of the lithium metal, the average internal resistance of the new battery is 3.45V, and the pulse voltage at -40℃ after high-temperature storage is 2.07V. Compared with Experimental Example 1, the changes in battery internal resistance and pulse voltage are the same. This indicates that having a diameter larger than the diameter of the modified film on the negative electrode surface does not significantly optimize battery characteristics, but instead leads to increased costs.
[0034] Examples 8-12 and Comparative Examples 6-7 verify the surface density gradient of the modified film on the negative electrode surface. The only difference between Examples 8-12 and Comparative Examples 6-7 and Example 1 is the surface density of the modified film on the negative electrode surface, as shown in Table 3. Table 3
[0035] As can be seen from the comparison of Examples 8-11 in Table 3, both the battery internal resistance and the low-temperature pulse discharge voltage after storage improved after increasing the surface density of the negative electrode modified film. In Comparative Example 7, the average internal resistance of the new battery was 3.72Ω, the average internal resistance after high-temperature storage was 6.32Ω, and the pulse voltage at -40℃ was 1.92V. The average internal resistance of the battery in Comparative Example 7 was larger than that in Examples 8-11, and the pulse voltage was significantly lower. This indicates that when the surface density of the negative electrode modified film is too small, the ion transport channels constructed by the carbon material inside the battery and the promotion of SEI formation by the additives are insufficient. Comparative Example 6 shows that further increasing the surface density of the negative electrode modified film did not significantly improve the battery internal resistance and pulse voltage. On the contrary, the increased thickness of the negative electrode modified film and the excessive amount of additives led to a decrease in the battery pulse voltage and an increase in battery height. Therefore, based on the comprehensive experimental results, the surface density of the negative electrode modified film was set at 8-13 g / m³. 2 This is the optimal choice.
[0036] In summary, adding a modified negative electrode surface film inside the battery creates a more stable SEI film and ion transport channels, reducing internal impedance and side reactions after high-temperature storage, thus maintaining a high pulse voltage even at low temperatures. Conductive carbon materials in the modified negative electrode surface film provide ion pathways, while additives (sulfonamides or sulfonylimides) promote SEI film formation. However, since sulfonamides or sulfonylimides cannot participate in ion channel construction, the ratio of conductive carbon materials to additives needs optimization. Comparative verification shows that a 1:1 ratio of conductive carbon material to additives is optimal. When the amount of conductive carbon material increases and the amount of additives decreases, the stability of the SEI film inside the battery decreases, resulting in a lower pulse voltage after high-temperature storage. When the proportion of additives is too high, the internal impedance of the battery increases, the ion migration rate decreases, leading to an increase in internal resistance and a decrease in pulse voltage. Therefore, the lithium primary battery prepared using the process of this invention exhibits excellent high-temperature storage stability and low-temperature discharge performance, while also having lower production costs.
[0037] The present invention adds a negative electrode surface modification film inside a lithium primary battery. The thickness of the negative electrode surface modification film is adjusted according to the model of the lithium primary battery so that the thickness of the assembled lithium primary battery does not exceed the limit specified in GB-T 8897.2-2021 "Primary Batteries - Part 2: Dimensions and Electrical Performance Requirements".
[0038] Meanwhile, since the additives in the negative electrode surface modification film react with lithium metal, if the diameter of the negative electrode surface modification film is larger than that of the negative electrode lithium sheet, a portion of it will not participate in the reaction, resulting in material waste.
[0039] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent process transformations made using the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A primary lithium battery, characterized in that: It includes a negative electrode cap and a positive electrode shell that interlock, with a negative electrode lithium sheet, a separator, a positive electrode sheet, and a current collector sequentially disposed between the negative electrode cap and the positive electrode shell. A negative electrode surface modification film is disposed between the negative electrode lithium sheet and the separator, and the areal density of the negative electrode surface modification film is 5-21 g / m³. 2 The modified film on the negative electrode surface is prepared using raw materials in the following weight ratio, with each component expressed in parts by weight: Conductive carbon material 2.4–4.8%; Adhesive 0.02-0.1%; Additives 2.4-4.8%; Solvent content: 90.3%–95.1%; The conductive carbon material comprises any one or more combinations of graphite, acetylene black, Ketjen black, graphene, carbon nanotubes, and porous carbon; the binder comprises at least one of polyvinylidene fluoride, nitrile rubber, polystyrene-butadiene rubber, and polytetrafluoroethylene; the additive is a sulfonamide compound or a sulfonylimide compound; and the solvent is one or more combinations of water, methanol, ethanol, propanol, isopropanol, and N-methylpyrrolidone. The preparation method of the negative electrode surface modified film includes: 1) weighing each raw material according to the raw material ratio, first adding the binder to the solvent, then adding the conductive carbon material to the solvent and mixing it evenly, and then adding the additive and mixing it evenly to obtain a slurry; 2) drying the slurry obtained in step 1), and pressing the dried powder into a solid film at a dew point of -40°C.
2. The lithium primary battery according to claim 1, characterized in that: Step 2) of the method for preparing the modified film on the negative electrode surface is to spray the slurry obtained in step 1) onto the surface of the negative electrode lithium sheet, and then dry it to form a thin film attached to the surface of the negative electrode lithium sheet.
3. The lithium primary battery according to claim 1, characterized in that: The additive is any one of p-nitrobenzenesulfonamide, p-chlorobenzenesulfonamide, and o-benzoylsulfonamide.
4. The lithium primary battery according to claim 1, characterized in that: The mass ratio of the conductive carbon material to the additive is 1:
1.
5. The lithium primary battery according to claim 1, characterized in that: The areal density of the modified film on the negative electrode surface is 8–13 g / m³. 2 .
6. The lithium primary battery according to claim 1, characterized in that: The diameter of the modified film on the negative electrode surface is not greater than the diameter of the negative electrode lithium sheet.
Citation Information
Patent Citations
Lithium primary battery and method for producing same
CN101877410B
Additive and electrolyte and lithium ion battery using same
CN114188607A
